The Role of Intelligence in the Process of Radicalization and its Impact on Acts of Terrorism: an Analysis of the Staircase to the Terrorist Act - Sugiarta, Yannisa Rakhmani; Sutanto, Rudy; Timur, Fauzia Gustarina Cempaka (PT FORMOSA CENDEKIA GLOBAL, 2024)
The process of radicalization and acts of terrorism is a complex phenomenon that affects global security. This article presents an analysis of the role of intelligence in addressing radicalization processes and acts of terrorism, particularly in the context of the Bali bombings. The research method used is a qualitative descriptive method with data collection techniques in the form of literature studies. The results showed the importance of the role of intelligence in tackling radicalization and acts of terrorism. With effective intelligence work, the risk of terrorism can be reduced and public security can be maintained. Analysis of the Bali bombing case also shows the complexity of the radicalization process and the need for timely and accurate preventive measures.